Taxonomic studies on the wasp families ampulicidae and sphecidae (hymenopterra: apoidea) of southern western ghats and its adjacent areas - Anagha S (Zoological Survey of India, Western Ghat Regional Centre, 2023)
Ampulicidae and Sphecidae are highly significant groups of apoidean wasp families of order Hymenoptera that play an important role in regulating population dynamics of some of the arthropod pest species. These wasps follow a predatory life to feed their developing larva with paralysed prey. Ampulicids are found to attack vexatious cockroaches, while sphecids on spiders, caterpillars, grasshoppers, crickets, katydids, most of which are pests of important crops. Thus, these wasps have the potential to be used in biocontrol programs. However, it is also important to note that, certain spider-hunting sphecids can inflict notable harm to agricultural ecosystems as spiders play a crucial role in controlling various crop pests. This emphasizes the need for a delicate balance in utilising biocontrol agents effectively. Bingham’s work (1897) happens to be the first basic study on Indian apoid wasps although changes in nomenclature have rendered it outdated. With few scattered reports and no valid revisionary work, the taxonomic studies of ampulicids and sphecids from India are still the least scanty. This void in research was the driving force behind the initiation of the present study, aiming to address and contribute to the understanding of these important insect groups.The present investigation is attempted to understand the taxonomic diversity and vicariance to two families Ampulicidae and Sphecidae from one of the biodiversity's treasure troves of India viz., "southern Western Ghats, and its adjacent areas". The study uncovered a total of 16 species belonging to three genera in two subfamilies of family Ampulicidae and a total of 17 taxa (species and subspecies) belonging to seven genera in four subfamilies of family Sphecidae. Three ampulicid species new to science namely, Ampulex sadiyae, Dolichurus chareshi, and Dolichurus sahyadriensis were described and published. Two species Dolichurus aridulus Krombein (family Ampulicidae) and Chalybion gracile Hensen (family Sphecidae) and a subspecies Sceliphron madraspatanum formosanum van der Vecht (family Sphecidae) were recorded for first time from India. Type specimens from Natural History Museum, London, UK, Oxford University Museum of Natural History, UK, and Zoological Museum, Copenhagen, Denmark were studied and redescriptions are provided for taxa with poor descriptions. This study also provides dichotomous key of all the Indian ampulicids and sphecids genera illustrating all the species found from the southern Western Ghats. Distribution map to species of all genera collected in family Ampulicidae and Sphecidae were made using QGIS online software. The present study led to the publication of four international papers, two national papers, three book chapters, and two online publications.
Thesis (Ph.D)- Western Ghat Regional Centre, Zoological Survey Of India, 2023